Atmospheric temperature and pressure influence the onset of spontaneous pneumothorax. (12th October 2016) - Motono, Nozomu; Maeda, Sumiko; Honda, Ryumon; Tanaka, Makoto; Machida, Yuichiro; Usuda, Katsuo; Sagawa, Motoyasu; Uramoto, Hidetaka
Abstract: Background: The aim of the study was to examine the influence of the changes in the atmospheric temperature (ATemp) and the atmospheric pressure (APres) on the occurrence of a spontaneous pneumothorax (SP). Patients and methods: From January 2000 to March 2014, 192 consecutive SP events were examined. The ATemp and APres data at the onset of SP, as well as those data at 12, 24, 36, 48, 60, and 72 h prior to the onset time, were analyzed. Results: The frequencies of SP occurrence were not statistically different according to the months or seasons, but were statistically different according to the time period ( P < .01) and SP events occurred most frequently from 12:00 to 18:00. SP events frequently occurred at an ATemp of 25 degrees Celsius or higher. There was a significantly negative correlation between the APres and the ATemp at the SP onset time. The values of change in the APres from 36 to 24 h prior to SP onset were significantly lower than the preceding values. Conclusions: In this study, we observed that a SP event was likely to occur in the time period from 12:00 to 18:00, at an ATemp of 25 degrees Celsius or higher, and at 24–36 h after a drop of APres.